Statistical thinking for managers - Hildebrand, David K.; Ott, R. Lyman (Pacific Grove, CA : Duxbury Press, 1998)
Data. Summarizing data about one variable. A first look at probability. Random variables and probability distribuitons. Random sampling and sampling distributions. Estimation. Hypothesis testing. Comparing two samples...
Keywords: Statistical methods; Industrial management; Statistics -- Data processing; Industrial management -- Statistical methods; Industrial management -- Statistical methods -- Data processing; Economics -- Statistical methods